A cross sectional study on factors associated with risk perception of healthcare workers toward healthcare waste management in health care facilities of Gondar Town, Northwest Ethiopia - Yenesew, Muluken Azage; Moges, Haimanot Gebrehiwot; Woldeyohannes, Solomon Meseret (International Journal of Infection Control, 2012)
Some of healthcare wastes are potentially dangerous to human health and contaminate the environment. Nonetheless, all types of healthcare wastes generated from healthcare facilities in many developing countries including Ethiopia are treated and managed equally like other ordinary general wastes by healthcare workers. Therefore, the aim of this study was to assess the risk perceptions of healthcare workers towards healthcare waste in healthcare facilities of Gondar town. A cross sectional study was employed to assess the risk perception of healthcare workers towards to healthcare wastes from April to May 2011. A total of 260 healthcare workers were included using simple random sampling technique. A self administered questionnaire was used to collect data. Data were entered and analyzed using SPSS version 16. Mean score was used to assess the risk perception of healthcare workers. Of the respondents, only 156 (60%) had scored greater than or equal to the mean score value on the risk perceptions of healthcare workers towards improper healthcare waste management. Knowledge on healthcare waste types (AOR: 9.04; 95%CI: 1.03, 79.23) and diseases transmitted with healthcare waste (AOR: 2.28; 95%CI: 1.08, 4.81), and having a training (AOR: 1.87; 95%CI: 1.03, 3.40) on the regarding Health Care Waste were significantly associated with risk perception of HCWs. None of the facilities had healthcare waste management guidelines. Only small proportion of the Healthcare workers had adequate risk perception on healthcare waste. Regular training on healthcare waste should be offered to improve the risk perceptions of healthcare workers and Health Care Facilities should have healthcare waste management plan and guidelines. Key words: Risk perceptions, Healthcare Workers, Healthcare Facilities